A estratégia territorial da Colônia Militar do Itapura: legado urbano e arquitetônico - Ghirardello, Nilson [UNESP]; Ferrari, Daniel Candeloro [UNESP] (Museu Paulista, Universidade de São Paulo, 2020)
In the mid-nineteenth century the imperial government employed a plan of occupation of the national territory through the creation of military colonies. Thus, the foundation of these settlements throughout the empire is connected to the problems related to social control and domination, at a time when the maintenance of territorial integrity and, at the same period, a perspective of expansion of the frontiers were posed as most urgent among the tasks of political elites. Itapura and Avanhandava were the two colonies in the province of São Paulo and inherited the homonyms of their strategic implantation sites - the waterfalls of the Tietê river. This paper aims to study the military colony of Itapura in its spatial-constructive aspect. The objective is to analyze the textual and cartographic material of the colony, documentation collected in public archives, mainly plans and projects, bringing to light such primary source. Therefore, with an evident intention of urban planning, it demonstrates that was an ideal that was beyond demarcating and occupying the territory: the aim was to build a projected city, initially with military character and on the banks of the Tietê, which would be the seed of future civil nucleus. Moreover, by comparing the plans of the 19th century colony with the images of its ruins, photographed by the Geographical and Geological Committee of São Paulo in the early 20thcentury, we can verify the architectural exuberance of your buildings and the urban quality of your plan, which is considered innovative for the age.

Em meados do século XIX o governo imperial empregou um plano de ocupação do território nacional através da criação de colônias militares. Assim, a fundação desses estabelecimentos por todo o império vincula-se aos problemas relacionados ao controle e domínio social, numa época em que a manutenção da integridade territorial e, simultaneamente, uma perspectiva de expansão das fronteiras colocaram-se como sendo das mais emergenciais entre as tarefas das elites políticas. Itapura e Avanhandava foram as duas colônias criadas na província de São Paulo e herdaram o topônimo de seus locais estratégicos de implantação - os saltos no Rio Tietê. O presente trabalho tem como propósito estudar a colônia militar do Itapura em seu aspecto espacial-construtivo. O objetivo é analisar o material textual e cartográfico da colônia, documentação coletada em arquivos públicos, principalmente plantas e projetos, trazendo à luz tal fonte primária. Dessa forma, com clara intenção de planejamento urbanístico, demonstra-se um ideal que estava muito além de demarcar e ocupar a região: o intuito era construir em meio à mata fechada e às margens do Rio Tietê uma cidade projetada, inicialmente de caráter militar e agrícola, que seria a semente de futuro núcleo civil. Além disso, ao compararem-se as plantas da colônia do século XIX com as imagens de suas ruínas, fotografadas pela Comissão Geográfica e Geológica de São Paulo no início no século XX, verifica-se a exuberância arquitetônica de suas construções e a qualidade urbanística de seu plano considerado inovador para a época.
Itapura’s military colony territorial strategy: urban and architectural legacy
Keywords: Military colony; Itapura; Avanhandava; Military colonization; Paulista territorial occupation; Colônia militar; Itapura; Avanhandava; Colonização militar; Ocupação territorial paulista